Artificial Bacterial Flagella for Remote‐Controlled Targeted Single‐Cell Drug Delivery. Issue 10 (10th March 2014) - Mhanna, Rami; Qiu, Famin; Zhang, Li; Ding, Yun; Sugihara, Kaori; Zenobi‐Wong, Marcy; Nelson, Bradley J.
<x xml:space="preserve">Abstract</x> An approach for batch preparation of liposome‐functionalized microdevices is demonstrated for remotely controlled single‐cell drug delivery. The liposome functionalized artificial bacterial flagella exhibit corkscrew swimming in 3D with micrometer positioning precision by applying an external rotating magnetic field. The devices are also capable of delivering water‐soluble drugs to single cells in vitro. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>